Cranial differentiation and evolution in Thrichomys apereoides (Rodentia: Echimyidae) - Bandouk, A. C.; dosReis, S. F.; Bordin, B. (Oxford University Press, 1996)
Thrichomys apereoides is an echimyid rodent which ranges in distribution from north-eastern and central Brazil into Paraguay, and currently five subspecies are recognized. Recent morphometric analyses of population samples formally assignable to T. a. laurentius and T. a. inermis, which occur in north-eastern Brazil, have shown that a major group of populations including both subspecies differ in cranial shape from a single population allocated to T. a. laurentius. In this study we employed mathematical models of evolutionary quantitative genetics to assess the role that random drift and selection may have played in the evolution of cranial shape differences in T. apereoides. The hypothesis of evolution due to drift was rejected and the selective forces necessary to account for shape differences were estimated. Minimum selective mortalities of the order of 10(-3) per generation were sufficient to explain the observed morphologic differentiation.